Experimental contact sensitivity - Kataranovski, M... (Acta dermatovenerologica Alpina, Pannonica et Adriatica, 2001)
In the present study, experimental model of contact sensitivity to dinitrochlorobenzene (DNCB) in inbred AO rats was employed to determine both antigen (hapten)-specific as well as parameters of antigennon-specific aspectsof contact hypersensitivity (CHS) response. Following local epicutaneous application of 2% DNCB, increased spontaneous, hapten-stimulated and interleukin (IL)-2-driven draining lymph node cell (DLNC) proliferation was detected, reflecting the antigen (hapten)-specific aspect of CHS. Changes in the ratio of lymphocyte subsets were noted in DLNC in the sensitization phase of CHS. At the dose of DNCB employed for the elicitation of CHS in sensitized animals, increased activity of peripheral blood granulocytes (including activation, adhesion and cell survival) was detected. Collectively,these data demonstrate the activation of both antigen (hapten)-specific and innate immunity in contact hypersensitivity. The importance of studying both mechanisms in this same model has been discussed.
Keywords: Cd4-cd8 ratio; Chemically induced; Dermatitis, contact; Dinitrochlorobenzene; Flow cytometry; Granulocytes; Immunology; Lymph nodes; Lymphocyte transformation